How Expansion of Public Services Affects the Poor: Benefit Incidence Analysis for the Lao People's Democratic Republic - Peter Warr; Jayant Menon; Sitthiroth Rasphone (Asian Development Bank (ADB), 2013)
Studies of the incidence of benefits from public services have rightly stressed the difference between average and marginal benefits. Cross sectional methods of analysis for Lao PDR indicate that for public education and health services, total benefits are highest for the best-off quintile groups. Nevertheless, these groups' shares of marginal benefits are generally considerably lower and the marginal benefit shares of poorer quintile groups are correspondingly higher. For primary and secondary education and for primary health centers, expanding the overall level of provision delivers a pattern of marginal benefits that is significantly more pro-poor than average shares indicate. Although panel estimates show a pattern of marginal benefits that is somewhat less pro-poor than cross-sectional results suggest, they do not change the finding that the pattern of marginal benefits is more pro-poor than the overall pattern of average benefits.
hdl:11540/2099
Keywords: D12; E21; H31; 330; benefit incidence analysis; average benefit; marginal benefit; health services; education services; Lao PDR